(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Early ontomorphogenetic specialization of Gymnospermium оdessanum (DC.) Takch. as ephemeroid geophyte has been recorded. Its extrapolation on the phylogenetic level as a ascertaining of the relative evolutional statics of the species was proposed.